Governing international rivers : polycentric politics in the Mekong and the Rhine - Myint, Tun. (Cheltenham, UK : Edward Elgar, 2012)
This important book employs the theory of polycentricity, a system with several centres as an analytical concept to explain the multilayered international environmental governance of river basins. It introduces a new methodological framework to deconstruct and investigate the dynamics of citizens, states and non-state actors in world politics via the context of river basin governance. The methodology is tested through in-depth field-based case studies, illustrating how local citizens and industries in the Mekong and Rhine river basins participate in transnational environmental governance at both local and international levels. Tun Myint expertly presents both a methodology and theory to conceive polycentricity of world politics as a major intellectual milestone in theorizing world politics. Providing nuanced details of cases showing the challenges and feasibilities of incorporating multiple actors into a governance framework, the book provides careful analysis into the power of non-state actors. -- Publisher description.
Governance and international rivers -- Polycentricity of world politics -- Institutional evolution in the Mekong and the Rhine -- Multilayer environmental governance in the Rhine -- Influence of non-state actors in governance of the Rhine -- Issues, interests and actors in the Pak Mun Dam project -- Influence of non-state actors on Pak Mun Dam -- Polycentric environmental governance.
Includes bibliographical references : (pages 240-254) and index.
Keywords: International rivers; Mekong River Watershed -- International status; Rhine River Watershed -- International status